The machine age of customer insight - Einhorn, Martin; Loffler, Michael; Bellis, Emanuel; Herrmann, Andreas; Burghartz, Pia (Emerald Publishing Limited, 2021)
We are living in a new machine age offering unique opportunities, particularly for generating customer insights, which is radically transforming the way business value is created. Across industries, players are affected by the pace of progress of machine learning tools, novel technologies, and the abundance of data. These developments require mastering new capabilities. 'The Machine Age of Customer Insight' explains the transformation of customer insights and demonstrates the growing impact of machine learning. Thought leaders from renowned universities in the US and Europe as well as from different industries provide a comprehensive overview. Addressing both academics and practitioners, they discuss the transformation, cutting edge tools, and success factors to thrive in the new age. The book shows how machine learning helps to understand customers better and faster. It supports everyone who considers the machine age a great opportunity to gain a competitive advantage by transforming customer insights into business value.